Adaptive Governance and Institutional System Strengthening in Stunting Prevention in Makassar City: Supporting Healthcare Service Accessibility - Irwansyah Irwansyah; Qamal Qamal (Jurnal Pemerintahan dan Politik Lokal, 2026)
This study aims to analyze how adaptive governance and institutional strengthening can enhance the effectiveness of stunting prevention policies, particularly in addressing limited access to health services a key contributing factor to the increase in stunting. This study adopted a qualitative approach, collecting data through interviews, observation, documentation, and Focus Group Discussions (FGDs). Data were analyzed using NVivo 12 Plus. The findings indicate that adaptive governance and institutional strengthening in Makassar City play a significant role in improving access to health services for stunting prevention, despite challenges such as incomplete cross-sectoral synergy, low community participation in densely populated and impoverished areas, and uneven distribution of health workers and integrated health post (Posyandu) facilities. Adaptive governance practices are emerging through the use of information technology for data collection on pregnant women and toddlers, multi-stakeholder collaboration forums, and the empowerment of Posyandu cadres. Data-based monitoring systems and cross-sector collaboration support more targeted and innovative interventions. Therefore, the implementation of adaptive governance and institutional strengthening constitutes a key strategy for ensuring more effective, responsive, and inclusive stunting prevention policies for all vulnerable groups in Makassar City.